How do streetcar transit users and streetcar decision-makers perceive heat risk? - Ida Sami; Ladd Keith (Journal of Public Transportation, 2023)
The thermal comfort perceptions of transit users at streetcar stops are critical to their overall ridership experience and health. Extreme heat is increasing due to climate change and the urban heat island effect, exposing transit users to greater heat stress. Through a survey of streetcar users and interviews with streetcar decision-makers, we explored the outdoor thermal comfort perceptions and transit stop design preferences of the Sun Link streetcar in Tucson, Arizona. Perceptions of heat among streetcar users varied by stop, with survey data revealing that 82.4 % of users reported feeling hot at the stops. Additionally, 56.08 % of users surveyed reported that more shade and trees would improve their thermal comfort. Heat risk is recognized by most decision-makers at Sun Link streetcar, primarily for their employees but also for users. Decision-makers reported needing additional resources to address transit user heat risk. We recommend increased awareness about extreme heat and heat resilience strategies at the stops, such as more shade and more frequent service, to help improve users’ thermal experience. Other transit systems facing increasing heat should also consider increasing heat risks and the thermal comfort perceptions of their users.